Biosorptionally treated dye wastewater employed in "Olla-pot coupled microbial fuel cell" for tomato (Solanum lycopersicum L.) irrigation and bio-electricity production. (February 2021) - Man mohan, K.; V, Kiran Kumar; Harindran, Sreevidya. V.; Gajalakshmi, S.
Abstract: This study presents a novel amalgamation of biosorption, Olla-Pot (OP) irrigation, and microbial fuel cells for the development of sustainable technology to remediate dye wastewater and reuse for crop irrigation and bioelectricity production. Biosorption of acid blue 193 dye on spent tea waste was carried out, and biosorptionally treated wastewater (TW) was employed in "Olla-Pots" for tomato irrigation. Additionally, Olla-pots has been infused with MFCs to take advantage of the organic load of TW to generate electricity. In biosorption studies, the Langmuir isotherm model was found to be the best fit (R 2 =0.9973) with maximum dye uptake capacity of 35.972 mg/g at 298 K. The Olla-pot MFC achieved 66.38 ± 1.58% of COD removal efficiency and 2.23 mW/m 2 of power density with TW. This approach of using biosorptionally treated wastewater in an ancient and simple irrigation technique can become a suitable option for the interlinking of efficient wastewater treatment and water conservation strategy. Graphical abstract: Unlabelled Image Highlights: Integration of biosorption, subsurface irrigation and green energy technology Maximum uptake capacity of spent tea dust waste for AB-193 was 35.97 mg/g. Novel Olla-Pot coupled MFCs design for post-sorption use of treated waste water Olla-pots showed maximum power density of 2.23 mW/m 2 .